Insect Diversity in Organic Rice Field Areas in Sumberjambe: Keanekaragaman Serangga Pada Area Sawah Organik Di Sumberjambe - Awaluddin, Ahmad Rusdy; Priantari, Ika; Afrida, Indah Rachmawati (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2024)
This study aimed to analyze insect diversity in organic rice fields planted with white and black rice varieties. Yellow pan traps were used to collect insects, with six traps placed in each field. The traps, consisting of 12 cm yellow bowls filled with a 70% alcohol-soap solution, were mounted on 30 cm bamboo sticks and secured with double-sided tape. Sampling was conducted over nine weeks at three intervals (weeks 3, 6, and 9), with three replicates per week. Collected insects were carefully removed using a brush, preserved in bottles containing 70% alcohol, and labeled for plot identification. In the first week, insects in white rice fields included Asilidae, Tachinidae, Chrysomelidae, Syrphidae, and Tipulidae, while black rice fields contained Asilidae, Tachinidae, Sphecidae, Ichneumonidae, Chrysomelidae, and Coccinellidae. By the second week, white rice fields had Tachinidae, Asilidae, Sphecidae, Chrysomelidae, and Hesperiidae, while black rice fields had Tachinidae, Hesperiidae, Ichneumonidae, and Chrysomelidae. In the third week, white rice fields hosted Tachinidae, Ichneumonidae, Hesperiidae, Sphecidae, Coccinellidae, and Chrysomelidae, whereas black rice fields included Tachinidae, Halictidae, and Sphecidae.